Analysing International Trade Patterns:: Comparative Advantage for the World’s Major Economies - Acharya, Ram (Journal of Comparative International Management)

(untitled) (None, 2008)
Using disaggregate product data classified by the Harmonized System code, this paper computes the revealed comparative advantage (RCA) for seven major economies that, when combined, contributed more than 80% of global manufacturing exports in 1996-97 and 2006-07. Results show that in the last decade, Canada, the US, and Japan have lost their share of global exports, while China has increased its share three-fold. These losses occurred mainly for low-tech products for the US, but medium and high-tech (MHT) products for Canada and Japan. However, MHT products comprise the highest share of Japanese exports (70%) compared to Canada (which has the lowest share, approximately half of Japan’s). Canada is the only economy whose contribution to global MHT exports is lower than that of global total exports. Japan also has the highest share of RCA-based MHT exports of other East Asian countries (OEACs) and the US. China has the highest share of non-RCA- based MHT exports. Finally, the trade patterns for OEACs and Mexico did not change greatly in any dimension in the last decade. However, products with RCA have changed substantially in all economies, with the highest in Mexico.